West Africa - Agricultural trade policy debates and developments: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
This Executive Brief focuses on 2012-13 developments in the West African agricultural sector. It highlights production and trade trends of some major products imported into the region (such as cereals, dairy products, poultry, beef and onions), and of some export products (cocoa, cotton, banana and palm oil). The brief analyses the recent developments in the regional integration process, including the finalized agreement on a joint common external tariff (CET) between ECOWAS and UEMOA, which now poses further challenges for the regional harmonization of tariff policies, and the negotiations for the regional EPA agreement with the EU.